2016
DOI: 10.1158/1078-0432.ccr-15-3054
|View full text |Cite
|
Sign up to set email alerts
|

Of Mice and Melanoma: PDX System for Modeling Personalized Medicine

Abstract: Summary Targeted therapies have advanced the treatment options for cutaneous melanoma but many patients will progress on drug. Patient-derived xenografts (PDX) can be used to recapitulate therapy resistant tumors. Furthermore, PDX modeling can be utilized in combination with targeted sequencing and phospho-proteomic platforms providing pre-clinical basis for second-line targeted inhibitor strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…Although the use of PDXs in routine diagnostic may not be a realistic goal due to variability in engraftment, latency period, number of animals required and costs [14], they may provide an unlimited resource of tumor cells for both small-scale as well as large-scale ex vivo drug screening. Here we demonstrated that PDXs assessed for treatment responses using the ex vivo assay show a high degree of concordance with results observed when analyzing the corresponding patient tumors directly, or when treating PDXs in vivo, supporting previous observations that early PDX passages resemble the original tumor [59]. In agreement with our findings, short-time ex vivo cultures of breast cancer PDXs were recently found to predict in vivo drug responses [60].…”
Section: Discussionsupporting
confidence: 90%
“…Although the use of PDXs in routine diagnostic may not be a realistic goal due to variability in engraftment, latency period, number of animals required and costs [14], they may provide an unlimited resource of tumor cells for both small-scale as well as large-scale ex vivo drug screening. Here we demonstrated that PDXs assessed for treatment responses using the ex vivo assay show a high degree of concordance with results observed when analyzing the corresponding patient tumors directly, or when treating PDXs in vivo, supporting previous observations that early PDX passages resemble the original tumor [59]. In agreement with our findings, short-time ex vivo cultures of breast cancer PDXs were recently found to predict in vivo drug responses [60].…”
Section: Discussionsupporting
confidence: 90%
“…Spontaneous melanoma is very rare in mouse, but the model is notably used as a support for patient-derived xenografts (PDXs) in immunocompromised animals. PDX mice properly model the human disease and can guide personalized therapy decisions ( Hartsough and Aplin, 2016 ). Another essential application of mouse as a model is the relatively easy manipulation of its genome.…”
Section: Animal Models Of Melanomamentioning
confidence: 99%
“…Mouse models applied for melanoma study have a long history [ 77 ] and exhibit several advantages compared to other animal models (fish, opossum, horse, dogs, pigs), such as: relevant known data concerning the genetic background which allows the possibility of genetic manipulation, easy breeding and handling, multiple studies about molecular pathways dissection, and representing appropriate hosts for patient-derived xenografts (PDXs) to develop semblable human disease and to establish personalized antimelanoma therapies [ 21 , 78 ].…”
Section: Murine Models Of Melanomamentioning
confidence: 99%